2022
DOI: 10.33087/jiubj.v22i3.2473
|View full text |Cite
|
Sign up to set email alerts
|

Kesadaran Halal Masyarakat terhadap Produk UMKM Makanan di Kota Bengkulu

Abstract: Currently, MSME products continue to increase and are not optimistic in the food sector. MSME food products are not in the form of packaging but also there are only MSME business actors who provide food directly on the spot and the food ingredients come from meat. According to LPPOM MUI data, there are 318 MSME products recorded in Bengkulu Province. 162 is located in Bengkulu City. Along with the development of the halal lifestyle, people are more selective in choosing food by paying attention to the availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Muslim dress is no longer a Muslim identity; it has become a social identity of Indonesian and global communities (Martiana et al, 2018). The concept of halal has a moral dimension and aims primarily at maintaining society and (Giyanti et al, 2020;Hossain & Quaddus, 2010;Wahyuni et al, 2022). Study related to halal modest fashion has also been found in many regions or countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muslim dress is no longer a Muslim identity; it has become a social identity of Indonesian and global communities (Martiana et al, 2018). The concept of halal has a moral dimension and aims primarily at maintaining society and (Giyanti et al, 2020;Hossain & Quaddus, 2010;Wahyuni et al, 2022). Study related to halal modest fashion has also been found in many regions or countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, research that focuses on Minang weaving has never been carried out in previous studies, especially in investigating the factors of technology, organization, and environment which then affect the readiness of companies to adopt halal. Some previous studies regarding the readiness of small-medium enterprises to implement halal practices and halal certification are as follows: Giyanti et al (2020) develop a measurement model to assess the readiness to implement halal in food-manufacturing SMEs, Wahyuni et al (2022) analyze the level of readiness of food products for halal certification, and (Jannah & Al-Banna (2021) examine food producers' halal awareness.…”
Section: Introductionmentioning
confidence: 99%